Minimal Inhibitory Concentration (MIC)-Phenomena in Candida albicans and Their Impact on the Diagnosis of Antifungal Resistance - Ulrike Binder; Maria Aigner; Brigitte Risslegger; Caroline Hörtnagl; Cornelia Lass-Flörl; Michaela Lackner (Journal of Fungi, 2019)
Antifungal susceptibility testing (AFST) of clinical isolates is a tool in routine diagnostics to facilitate decision making on optimal antifungal therapy. The minimal inhibitory concentration (MIC)-phenomena (trailing and paradoxical effects (PXE)) observed in AFST complicate the unambiguous and reproducible determination of MICs and the impact of these phenomena on in vivo outcome are not fully understood. We aimed to link the MIC-phenomena with in vivo treatment response using the alternative infection model Galleria mellonella. We found that Candida albicans strains exhibiting PXE for caspofungin (CAS) had variable treatment outcomes in the Galleria model. In contrast, C. albicans strains showing trailing for voriconazole failed to respond in vivo. Caspofungin- and voriconazole-susceptible C. albicans strains responded to the respective antifungal therapy in vivo. In conclusion, MIC data and subsequent susceptibility interpretation of strains exhibiting PXE and/or trailing should be carried out with caution, as both effects are linked to drug adaptation and treatment response is uncertain to predict.